2022
DOI: 10.1021/acs.joc.2c00870
|View full text |Cite
|
Sign up to set email alerts
|

Monofunctionalized Fluorinated Bambusurils and Their Conjugates for Anion Transport and Extraction

Abstract: Bambusurils are macrocyclic molecules that are known for their high binding affinity and selectivity toward anions. Here, we present the preparation of two bambusurils bearing fluorinated substituents and one carboxylic function. These monofunctionalized bambusurils were conjugated with crown ether and cholesterol units. The resulting conjugates were successfully tested in liquid–liquid extraction of inorganic salts and chloride/bicarbonate transport across lipid bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…Although with this method all the transporters showed similar activity, mechanistic studies revealed that bambusuril 35 d was clearly the most active transporter via a classical HCO 3 − /Cl − antiport mechanism (see Section 4.2 for a detailed discussion on mechanistic studies). Moreover, this compound also showed the best activity in HCO 3 − uniport experiments and performed in a follow‐up study with more bambusurils still the best, together with 35 k [88] . The special character of the bambusuril binding site (formed by polarized CH groups), the high anion affinity, the large degree of fluorination, and the possibility to accommodate two anions in its binding site are features that probably contribute to the exceptional transport properties of these fluorinated bambusurils.…”
Section: Overview Of Synthetic Bicarbonate Transportersmentioning
confidence: 85%
See 3 more Smart Citations
“…Although with this method all the transporters showed similar activity, mechanistic studies revealed that bambusuril 35 d was clearly the most active transporter via a classical HCO 3 − /Cl − antiport mechanism (see Section 4.2 for a detailed discussion on mechanistic studies). Moreover, this compound also showed the best activity in HCO 3 − uniport experiments and performed in a follow‐up study with more bambusurils still the best, together with 35 k [88] . The special character of the bambusuril binding site (formed by polarized CH groups), the high anion affinity, the large degree of fluorination, and the possibility to accommodate two anions in its binding site are features that probably contribute to the exceptional transport properties of these fluorinated bambusurils.…”
Section: Overview Of Synthetic Bicarbonate Transportersmentioning
confidence: 85%
“…Monofunctionalised analogues of 35 c and 35 d were also prepared and conjugated to cholic acid and crown‐ether moieties ( 35 e – k ). [88] These substituents showed only a marginal effect on the transport properties of the bambusurils. Bambusurils represent one of the most active and selective families of bicarbonate transporters (see Sections 3.5 and 4.1 for extended discussions).…”
Section: Overview Of Synthetic Bicarbonate Transportersmentioning
confidence: 99%
See 2 more Smart Citations
“…Monofunctionalised analogues of 35c and 35d were also prepared and conjugated to cholesterol and crown-ether moieties. 85 These substituents showed only a marginal effect on the transport properties of the bambusurils. Bambusurils represent one of the most active and selective families of bicarbonate transporters (see Sections 3.5 and 4.1 for extended discussions).…”
Section: Transporters Without Acidic Nh or Oh Groupsmentioning
confidence: 99%